Facial area and hairiness of pollinators visiting semi‐natural grassland wild plants predict their facial pollen load. (4th August 2020) - Goulnik, Jérémie; Plantureux, Sylvain; Van Reeth, Colin; Baude, Mathilde; Mesbahi, Geoffrey; Michelot‐Antalik, Alice
Abstract : 1. Consequences of a decline in pollination function in semi‐natural ecosystems are largely unknown due to variability in pollinator effectiveness, that is, their contribution to pollen deposition alone. While pollination effectiveness has been shown to be related to body size and hairiness of pollinators for some crops, studies encompassing a wide diversity of pollinators interacting with wild plant communities are lacking. 2. Thus, the relationships between pollen load, which is a measurement of pollen transport ability and a proxy of pollinator effectiveness, and morphological traits of pollinators sampled in 16 grasslands in Moselle, France, were investigated. The area, hairiness, and pollen load of each pollinator's face were measured for 658 individuals from 127 bee and fly species interacting with 36 wild plant species. Pollinator dry mass was also measured on 543 individuals from 109 species. 3. Dry body mass and facial area of pollinators were positively linked. This study highlights that bees transported significantly more pollen grains on their face than flies. Furthermore, bees' faces were larger and hairier. We also found that pollinators' facial pollen load increased with facial area and hairiness when we considered all pollinators. However, hairiness is not significant within pollinator group (bees or flies), mirroring a potential phylogenetic signal. 4. Hence, this study shows a wide diversity of pollinator and plant species in which larger and hairier pollinators may transport more pollen grains, at least on their face. However, future studies involving other pollinator body parts are needed to generalise these relationships. Abstract : Pollinator facial pollen load is explained by pollinator facial hairiness and area for 658 pollinators belonging to 127 species and interacting with 36 wild plant species However, hairiness is not significant when we include the pollinator group (i.e. flies or bees), mirroring a potential phylogenetic signal for this effect trait Our results confirm that pollinator hairiness and area are good candidates as pollination effect traits, yet these findings need to be generalized to other pollinator body parts